2018
DOI: 10.1126/scisignal.aal1601
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory but not mitogenic contexts prime synovial fibroblasts for compensatory signaling responses to p38 inhibition

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disorder that causes joint pain, swelling, and loss of function. Development of effective new drugs has proven challenging, in part because of the complexities and interconnected nature of intracellular signaling networks, which complicate the effects of pharmacological interventions. Here, we characterized the signaling pathways that are activated in RA and evaluated the multivariate effects of targeted inhibitors. Synovial fluids from RA patients activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 74 publications
0
20
1
Order By: Relevance
“…While most of these studies identified single, predominant mechanisms that were responsible for this crosstalk in specific cell types and under specific conditions, our quantitative measurements enabled us to quantitate the contribution of post-translational and transcriptional cross-inhibition in each response to various inflammatory and stress stimuli (Figure 2). Recently, Lauffenburger and his colleagues quantitatively demonstrated that p38 is a crucial factor for negative crosstalk to the JNK pathway under various conditions in synovial fibroblasts (Jones et al, 2018). The cross-inhibition by p38 generated cell-to-cell variability in JNK activity under all tested conditions, suggesting that this is a common mechanism underlying JNK and p38 signaling ( Figure 3C).…”
Section: Discussionmentioning
confidence: 89%
“…While most of these studies identified single, predominant mechanisms that were responsible for this crosstalk in specific cell types and under specific conditions, our quantitative measurements enabled us to quantitate the contribution of post-translational and transcriptional cross-inhibition in each response to various inflammatory and stress stimuli (Figure 2). Recently, Lauffenburger and his colleagues quantitatively demonstrated that p38 is a crucial factor for negative crosstalk to the JNK pathway under various conditions in synovial fibroblasts (Jones et al, 2018). The cross-inhibition by p38 generated cell-to-cell variability in JNK activity under all tested conditions, suggesting that this is a common mechanism underlying JNK and p38 signaling ( Figure 3C).…”
Section: Discussionmentioning
confidence: 89%
“…Although our results confirmed the mediatory role of the NF-kB pathway, we found that the inhibition of other MAPK pathways, specifically p38-MAPK, further enhanced IL-1a and IL-1b expression in RASFs. This is particularly of interest because a recent study by Jones et al (27) examined the potential reasons for the failure of p38 inhibitors in clinical trials for RA. The authors observed that the inhibition of p38 further activated "off-target" pathways, including NF-kB, JNK, and ERK, triggering a rapid induction of inflammation similar to that observed in cytokine-stimulated RASFs.…”
Section: Discussionmentioning
confidence: 99%
“…Because the p38 pathway plays an important role in inflammation, there was hope that inhibitors would show efficacy in the clinic. Nevertheless, systemic p38 inhibition in patients is associated with unacceptable side effects and tachyphylaxis [4,47], possibly due to feedback activation of NF-κB, JNK, and MEK signaling [48]. This limitation had led to the search for inhibitors that target other part of the p38 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%